(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2024)
PUTEM SVETLOSTI I SENAKA – HISTORICAL IN DIARY NOTES OF PETER ODAVIĆ The paper analyzes the unpublished diary entries of the judge, diplomat and writer Petar Odavić, kept at larger or smaller intervals for more than sixty years (1886–1947). The insu- fficiently known experiences, points of view and knowledge of a high-ranking, albeit disputed in society, intellectual on issues that were important for the national existence of the Serbs and their country are illuminated; attitude towards the Obrenovićs, the Serbian question, the Balkan Wars, the First World War, political relations in the Yugoslav state, Serbian-Croatian relations, artistic creativity as an expression of contradictions in Yugoslav society, the role of the Roman Catholic Church.